A preconditioned iterative solution scheme for nonlinear parabolic systems arising in air pollution modeling - Karatson, Janos; Kurics, Tamas (Mathematical Modelling and Analysis, 2013)
A preconditioned iterative solution method is presented for nonlinear parabolic transport systems. The ingredients are implicit Euler discretization in time and finite element discretization in space, then an outer-inner (outer damped inexact Newton method with inner preconditioned conjugate gradient) iteration, further, as a main part, preconditioning via an l-tuple of independent elliptic operators. Numerical results show that the suggested method works properly for a test problem in air pollution modeling.